Tafsir Al-Qur’an pada Masa Tābi‘īn dan Lahirnya Tafsir bi al-Ijtihād - Mawaddah Ahmad, Ida; Basri, Halimah; Amir Hamzah (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
The development of Qur'anic exegesis (tafsir) during the Tābiʿīn period represents a significant phase in the history of Qur'anic interpretation, serving as a bridge between the interpretive tradition of the Companions and the emergence of systematic exegetical methodologies in subsequent periods. During this era, Qur'anic interpretation evolved beyond mere transmission of reports (riwāyah) through the increasing application of ijtihād, while remaining grounded in the Qur'an, the Prophetic traditions, and the principles of the Arabic language. This study aims to examine the development of tafsir during the Tābiʿīn period, the characteristics of tafsīr bi al-ijtihād, and its contribution to the emergence of various exegetical trends in the Islamic intellectual tradition. This research employs a qualitative library research approach. Data were collected through documentary analysis of classical tafsir works, scholarly books, and relevant academic journal articles, and were analyzed using the content analysis method. The findings indicate that the Tābiʿīn period constituted a crucial transitional stage in the development of Qur'anic exegesis, marked by the establishment of major schools of tafsir, the wider application of ijtihād in interpreting Qur'anic verses, and the emergence of diverse exegetical orientations, including linguistic (lughawī), juridical (fiqhī), theological (kalāmī), philosophical (falsafī), and mystical (ṣūfī) exegesis. Consequently, the scholarly contributions of the Tābiʿīn laid the essential foundation for the subsequent development of Qur'anic exegesis and the rich diversity of Islamic exegetical methodologies.